Edible coating pati singkong (Manihot utilissima Pohl) terhadap mutu nenas terolah minimal selama penyimpanan - Satria Wati Pade (Jurnal Agercolere, 2019)
Pineapple is desirable to be consumed fresh, but it taking too long in stripping the pineapple's outer skin. Therefore, currently, the technology of processing horticultural products is minimally applied. Minimum fruit processing can speed up product shelf life. One way to overcome this is coating. Hydrocolloid edible coating is one type of coating with starch as the base material found in several types of tubers, one of which is cassava tuber. This study used a completely randomized design method consisting of one control sample and 3 treatments, cassava starch concentrations were repeated three times, namely A1: 3% cassava starch, A2: 4% cassava starch, A3: 5% cassava starch with 8 days observation. The variables observed were vitamin C, weight loss and color. The results showed that the highest vitamin C content was in the treatment of 5% cassava starch at 3.20 mg/100 g and the lowest was the control treatment of 3.15 mg/100 g. The smallest weight loss was A3 treatment of 73.75% and the biggest was control treatment 79.67%. The average value of the highest color was found in A3 treatment, which was around 66.92º showed yellow-red.